IMPLEMENTATION OF GREEN SCHOOL TOWARDS AN ENVIRONMENTALLY CARING SCHOOL AT ELEMENTARY SCHOOL MUHAMMADIYAH 1 KREMBUNG - Puspita Handayani; Aziza, Siti Nur; Ariyani Arief; Umyati; Afifah Dzati Sya’diyah; Muhammad Arif N. H (Antis-publisher, 2025)
Objective: Green school is a concept by holding greening in the school environment both indoors and outdoors which aims to maintain, maintain, build and care for the green environment. One of the activities is the greening of the school. The problems faced by partners are (1) there is still a lack of knowledge in the process of developing or utilizing land, (2) there is still a lack of awareness and concern for environmental management, (3) it is still less than optimal for greening so that the environmental atmosphere looks arid and barren. Therefore, the community service team of the Muhammadiyah Sidoarjo University education study program, tried to offer a solution, namely by inviting the entire extended family of SD Muhammadiyah 1 Krembung to contribute to implementing the green school program to lead to a school that cares about the environment, through socialization and education activities to students about the introduction of organic and inorganic waste and its use. Method: Implementation methods include observation, interview, preparation, implementation, and evaluation or monitoring. Results: The results achieved were that school residents, especially students, gained knowledge about the introduction of organic and inorganic waste and its use, namely making hanging and vertical pots from used bottles, planting plants in hanging and vertical pots, making pencil holders and flower vases to support SBDP learning and repairing ponds into ecological parks that can be used as science education media. To achieve the objectives of implementing the green school program, all school residents must be involved in maintaining cleanliness, care, and greening the school. Novelty: This is done as an effort so that the school environment does not produce much food waste or drinks, by processing it so that it can make a school that is truly a green school.